PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA ELEMEN PELAJARAN TEKNOLOGI JARINGAN KABEL DAN NIRKABEL DI SMK N 3 PARIAMAN - Rahmawati, Khairanti; Mary, Thomson; Kurniawan, Haris (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
The objective of this study is to develop interactive learning madia for SMK Negeri 3 Pariaman utilizing Lectora Inspire, with the aim of enhancing effectiveness and usefulness. The present study employs the research and development (RD) approach, which follows the ADDIE development model consisting of analysis, design, development, implementation, and evaluation stages. The learning tool incorporates a validation questionnaire sheet and a practicality sheet. The process of data collecting involves the administration of a validation questionnaire sheet to the validator, as well as the distribution of a practicality questionnaire page to both the teacher and students. The results of material validation conducted by experts in the field yielded an average score of 0.83, placing it inside the valid category. In comparison, the media validation conducted by professionals in the media field yielded an average score of 0.87. The practicality scores of teachers and students were analyzed, revealing an average score of 84% for teachers and 90% for students in the practicality area.